Oral Health Knowledge, Attitude, and Practices among School Teachers in Chitwan District, Nepal - Harender Singh; Sanjeeb Chaudhary; Abhishek Gupta; Anusha Bhatta (International Journal of Dentistry)
Background. Oral health is dependent on the knowledge and awareness of the individuals. Teachers as individuals influence the children in every aspect including oral health maintenance. The objective of this study was to assess the oral health knowledge, attitude, practices, and oral health status among school teachers in Chitwan District, Nepal. Materials and Methods. A cross-sectional study was conducted on 550 school teachers of private and government schools in Chitwan District, to assess the knowledge, attitude, practices, and oral health status. Descriptive analysis was done and data were analyzed using chi-square. A five-point Likert Scale was applied to compute knowledge, attitude, and practices of the school teachers. Results. Most of the school teachers had good knowledge about periodontal diseases in comparison to dental caries. Private school (20.7% : 57) teachers had higher good oral health knowledge as compared to government school teachers (9.8% : 27). An almost equal percentage of private and government teachers (73.5% : 202 and 74.2% : 204, respectively) were found with fair knowledge about oral health. Males had a higher percentage for good oral health knowledge as compared to females. Conclusion. There is an incredible need to improve oral health knowledge and attitude among school teachers concerning different problems of the oral cavity and the avoidance of dental diseases. These enhancements can be applied through regular training of teachers by oral health seminars, materials, and other such types of methods.